DETERMINING SALESPERSON PERFORMANCE EFFICIENCY IN PRIVATE BANK IN INDONESIA USING DATA ENVELOPMENT ANALYSIS (DEA) MODEL - Raihana Radian, Salsabila
The profitability of the banking business is determined by how well the salespeople are able to generate revenue. Bank Privat, a private-owned bank in Indonesia faced a challenge of discrepancy of performance. Although the same target distribution method has been applied throughout their branches in Indonesia, wide performance gap persists. This situation indicates difference in performance efficiency of salespeople or Relationship Managers across all branches of Bank Privat. The analysis focuses on the sixteen (16) Bank Privat branches located in Jakarta. Using two-stage Data Envelopment Analysis (DEA) model, the calculation considers input, intermediary measures, and output to be included based on the data acquired from each branch. As the performance result of each branch are heavily dependent on the salespeople, the number of Relationship Managers in each branch is considered as input variable. The activities they did by selling banking products to increase the amount of deposit, loan, and investment balance, and the number of new customers they acquire for the branch are considered as intermediary measures, as these activities will eventually yield in a desired output (revenue). Using the DEA model calculation score, some branches show perfect efficiency in processing input into intermediary measures, and intermediary measures into output. These branches are compared to those with non-perfect efficiency result and compared across three different perspectives to understand their reasons of disparity: demography, competency, and personality of the salespeople. Result shows branches with perfect efficiency have more Relationship Managers that are shorter in tenure and have experience in working for National Bank previously. The study also discussed the possibility of difference in personality trait between branches with perfect efficiency and non-perfect efficiency. Furthermore, based on the DEA model, the result can provide for future implementation in human capital improvement